Preclinical Evaluation of 18F-ML-10 to Determine Timing of Apoptotic Response to Chemotherapy in Solid Tumors. (10th January 2017) - Demirci, Emre; Ahmed, Rafay; Ocak, Meltem; Latoche, Joseph; Radelet, April; DeBlasio, Nicole; Mason, N. Scott; Anderson, Carolyn J.; Mountz, James M.
Purpose: We investigated 2-(5-fluoro-pentyl)-2-methyl-malonic acid ( 18 F-ML-10) positron emission tomography (PET) imaging of apoptosis posttherapy to determine optimal timing for predicting chemotherapy response in a mouse head/neck xenograft cancer model. Procedures: BALB/c nude mice (4-8 weeks old) were implanted with UM-SCC-22B tumors. The treatment group received 2 doses of doxorubicin (10 mg/kg, days 0, 2). Small animal 18 F-ML-10 PET/computed tomography was performed before and on days 1, 3, and 7 postchemotherapy. Using regions of interest around tumors, 18 F-ML-10 uptake change was measured as %ID/g and uptake relative to liver. Terminal Uridine Nick-End Labeling (TUNEL) immunohistochemistry assay was performed using tumor samples of baseline and on days 1, 3, and 7 posttreatment. Results: Treated mice demonstrated increased 18 F-ML-10 uptake compared to baseline and controls, and 10 of 13 mice showed tumor volume decreases. All control mice showed tumor volume increases. Tumor-to-liver (T/L) ratios from the control group mice did not show significant change from baseline ( P > .05); however, T/L ratios of the treatment group showed significant 18 F-ML-10 uptake differences from baseline compared to days 3 and 7 posttreatment ( P < .05), but no significant difference at 1 day posttreatment. Conclusion: 2-(5-Fluoro-pentyl)-2-methyl-malonic acid PET imaging has the potential for early assessment of treatment-induced apoptosis. Timing and image analysis strategies may require optimization, depending on the type of tumor and cancer treatment.